Energy Harvesting and Storage with Soft and Stretchable Materials. Issue 19 (27th January 2021) - Vallem, Veenasri; Sargolzaeiaval, Yasaman; Ozturk, Mehmet; Lai, Ying‐Chih; Dickey, Michael D.
Abstract: This review highlights various modes of converting ambient sources of energy into electricity using soft and stretchable materials. These mechanical properties are useful for emerging classes of stretchable electronics, e‐skins, bio‐integrated wearables, and soft robotics. The ability to harness energy from the environment allows these types of devices to be tetherless, thereby leading to a greater range of motion (in the case of robotics), better compliance (in the case of wearables and e‐skins), and increased application space (in the case of electronics). A variety of energy sources are available including mechanical (vibrations, human motion, wind/fluid motion), electromagnetic (radio frequency (RF), solar), and thermodynamic (chemical or thermal energy). This review briefly summarizes harvesting mechanisms and focuses on the materials' strategies to render such devices into soft or stretchable embodiments. Abstract : Methods to harvest ambient energy (mechanical, thermal, chemical, and electromagnetic energy) using soft and stretchable materials are summarized. These materials and devices pave the way for untethered soft robots, selfpowered sensors, wearable devices, stretchable electronics, and electronic skins. The challenges and opportunities associated with ambient energy harvesting techniques are also discussed.